2021
DOI: 10.3390/app11062796
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Physical and Rheological Properties of Trinidad Lake Asphalt Modified Binder

Abstract: Mastic asphalt (MA) has been recognized as one of the most deformation-resistant and thus durable materials for bridge pavement. The performance properties of MA are highly dependent on the physical and rheological properties of the binder applied in the MA mixture. To modify the binder properties to obtain the expected performance of the MA mixture, Trinidad Lake Asphalt (TLA) is often applied. In this study, the TLA-modified binders to be used in mastic asphalt bridge pavement systems were evaluated to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The additional results of a comprehensive laboratory investigation on the physical and rheological properties of the 35/50 base bitumen modified by the addition of three different TLA contents (0, 10, and 20% by weight) as well as on the effect of short-term ageing on these physical and rheological characteristics were presented by the authors elsewhere [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional results of a comprehensive laboratory investigation on the physical and rheological properties of the 35/50 base bitumen modified by the addition of three different TLA contents (0, 10, and 20% by weight) as well as on the effect of short-term ageing on these physical and rheological characteristics were presented by the authors elsewhere [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result of fitting ZSV to the static indentation is about 95%, the slightly worse relationship can be observed using the regression results for the dynamic indentation (90%). It is worth emphasizing that the authors carried out similar estimations for other test conditions: the TLA-modified binders in the original (unaged) state, creep test of ZSV instead of oscillatory test and three temperatures of ZSV test in the range of 40–60 °C [ 55 , 56 ]. The analysis revealed that not one of these considered test conditions had a significant influence on the static as well as dynamic indentation test results.…”
Section: Resultsmentioning
confidence: 99%
“…Trinidad lake asphalt (TLA) is the world's most famous, widely used natural bitumen [11]. Physical and rheological properties of TLA-modified bitumen showed that TLA could help to improve the stiffness [12], high-temperature stability [13], and low-temperature-induced cracks [14] of bitumen. Yang et al investigated the high-temperature properties of TLA modified asphalt, and the results indicated that the modified asphalt had higher resistance to rutting deformation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the structural strength of Gussasphalt concrete is greatly affected by the properties of the asphalt binder, which results in poor stability at high temperature and other distresses [ 14 ]. In order to form a stable mixture of skeleton structure and improve the high-temperature stability of the pouring asphalt mixture, a base penetration asphalt is added, such as Trinidad Lake Asphalt (TLA) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%